TEKNOLOJİ GELİŞTİRME BÖLGELERİNİ ETKİLEYEN YENİLİK EKOSİSTEM MODELİ - YOĞUNLU, ABDULVAHAP (Fırat Üniveristesi, 2021)
Teknoloji Geliştirme Bölgeleri (TGB) bilgi ve teknoloji temelli üretimlerin gerçekleştiği, üniversiteler başta olmak üzere ilgili yerel ve ulusal yapı ve aktörler ile karşılıklı etkileşim içerisinde faaliyetlerini yürüten yeni nesil üretim alanlarıdır. Bu üretim alanlarında küresel pazarın talep ettiği ürünleri üretmeyi hedefleyen ve küresel alanda rekabet imkânlarının sürekliliğini sağlamak isteyen girişimciler bulunur. Söz konusu girişimciler akademik alanda geliştirilen bilgiyi ticarileştirmeyi ve kendi yenilik fikirlerini akademik bilgi ile geliştirip rekabet gücü yüksek yenilikçi ürün ve hizmetler ortaya çıkarmayı hedefler. Bu anlamda, Teknoloji Geliştirme Bölgeleri birer yenilik üretim merkezleridir. Yenilik olgusu, bir canlı organizma gibi uygun bir çevre ve içerikte ortaya çıkar ve gelişir. Yenilik olgusunun doğup olgunlaşması; sosyal, siyasal ekonomik ve kültürel yapılar, kanuni düzenlemeler ve ilgili yerel ve ulusal aktörler ile ilişkisini kapsayan bir sistem çerçevesinde gerçekleşir. Bu karmaşık, çok boyutlu, çok aktörlü ve sürekli karşılıklı etkileşimin olduğu sistem yenilik ekosistemi olarak ifade edilir. Teknoloji Geliştirme Bölgeleri bir yenilik üretim merkezi niteliğinde oldukları için yenilik olgusu gibi uygun bir yenilik ekosisteminde doğar ve olgunlaşır. Teknoloji Geliştirme Bölgelerinin yaşam niteliğini Teknoloji Geliştirme Bölgesinin kurulduğu yerin yenilik ekosistemi doğrudan etkiler. Bu nedenle Teknoloji Geliştirme Bölgelerinin yeterli nitelik ve yetkinlikte yenilik ekosistemine sahip yerlerde planlanması gerekmektedir. Teknoloji ve bilgi temelli üretimler ulusal ve yerel kalkınmanın en önemli unsuru haline gelmiş ve yenilik olgusu günümüz küresel kapitalizminin temel dinamiği olmuştur. Bu bağlamda yenlik üretim alanları olan Teknoloji Geliştirme Bölgeleri dünyanın gelişmiş diğer ülkelerinde olduğu gibi, ülkemizde de son elli yılda sayıları artarak yaygınlaşmaya başlamışlardır. Özellikle yerel idareler kendi bölgelerinin sosyal ve ekonomik gelişimine katkı sunmak maksadı ile bölgelerinde Teknoloji Geliştirme Bölgesi kurulmasına yönelik faaliyetler yürütmektedir. Ülkemizde bu kuruluş talepleri 4691 Sayılı Teknoloji Geliştirme Bölgeleri Kanunu ve yönetmelikleri çerçevesinde değerlendirilmektedir. Ancak yapılan değerlendirmelerde Teknoloji Geliştirme Bölgelerinin yaşam niteliğini belirleyen yenilik ekosistem olgusunu temel alan bir yöntem söz konusu değildir. Bu çalışmada Teknoloji Geliştirme Bölgelerini etkileyen yenilik ekosistemi unsurları irdelenerek, yedi ana kriter başlığı altında yer alan 38 kriterden oluşturulan veri seti, Çok Kriterli Karar Verme tekniklerinden Entropi ve PROMETHEE yöntemleri kullanılarak 81 ilin yenilik ekosistem endeks sırası ortaya çıkarılmıştır. Ortaya çıkarılan yenilik ekosistem endeksi ve diğer yedi alt endeks sıralamaları ile ülkemizde Teknoloji Geliştirme Bölgesi bulunmayan 26 ilin Teknoloji Geliştirme Bölge kuruluş önceliklerini değerlendiren bir model oluşturulmuştur. Söz konusu model 81 ilin yenilik ekosistem özelliklerini karşılaştırma imkânı sunacak, yeni Teknoloji Geliştirme Bölgesi kuruluş taleplerinin objektif kriterler ile değerlendirilmesine katkı verecek ve böylece kamu yatırımı niteliğinde olan Teknoloji Geliştirme Bölgesi yatırımlarının atıl kalma riskleri önceden değerlendirilmiş olacaktır. Anahtar Kelimeler: Teknoloji Geliştirme Bölgeleri, Yenilik, Yenilik Ekosistemi, Kuruluş Yeri Kararı, Çok Kriterli Karar Verme Teknikleri

Technology Development Zones (TDZs) are the new generation creation areas where knowledge and technology-based production takes place, conducting their activities in mutual interaction with relevant local and national structures and actors, especially with universities. In these production areas, there are entrepreneurs who aim to produce the products demanded by the global market and want to ensure the continuity of their competitive opportunities in the global arena. These entrepreneurs aim to commercialize the knowledge developed the academic field by developing their own innovation ideas with academic knowledge to create highly competitive innovative products and services. In this sense, Technology Development Zones are innovation creation centers. The fact of innovation arises and develops in a suitable environment and content like a living organism. The emergence and maturation of the fact of innovation takes place within the framework of a system that includes social, political, economic and cultural structures, legal regulations and a relationship with relevant local and national actors. This complex, multi-dimensional, multi-actor and continuous interaction system is identified as an innovation ecosystem. Owing to the fact that Technology Development Zones are innovation creation centers, they are born and got mature in a suitable innovation ecosystem, such as the fact of innovation. The quality of life of the Technology Development Zones is directly affected by the innovation ecosystem of the location where the Technology Development Zone is established. For this reason, Technology Development Zones should be planned in places with adequate quality and competent innovation ecosystem. Technology and knowledge-based production have become the most important elements of national and local economic development, and the fact of innovation has become the main dynamic of today's global capitalism. In this context, Technology Development Zones, as innovation creation areas, have started to become widespread in Turkey in the last fifty years, like other developed countries of the world. Especially local governments carry out activities for the establishment of Technology Development Zones in their regions in order to contribute to the social and economic development of their regions. In Turkey, this organization claims are being evaluated within the scope of Technology Development Zones Law and complementary regulations. However, in the assessments made, there is no method based on the innovation ecosystem phenomenon that determines the life quality of Technology Development Zones. In our study, by examining the innovation ecosystem factors affecting the Technology Development Zones, the data set is formed by the use of 38 criteria under seven main criteria and by using Entropy and PROMETHEE methods of Multi-Criteria Decision Making techniques, the innovation ecosystem index order of 81 provinces is revealed. Via the innovation ecosystem index and the other seven sub-index rankings, a model his created that evaluates the Technology Development Zone establishment priorities of 26 provinces that do not have Technology Development Zone in Turkey. This model will provide the opportunity to compare the innovation ecosystem characteristics of 81 provinces, to contribute to the evaluation of the establishment demands of the new Technology Development Zone with objective criteria, and thus the risk of being inactive of the Technology Development Zone investments, which are public investments, will be assessed in advance. Key Words: Technology Development Zone, Innovation, Innovation Ecosystem, Facility Location Decision, Multi-Criteria Decision Making Techniques.
The innovation ecosystem model influencing on technology development zones
Keywords: Bilim ve Teknoloji; İşletme